Midwifery 2030: a woman's pathway to health. What does this mean?. (January 2016) - Hoope-Bender, Petra ten; Lopes, Sofia Tavares Castro; Nove, Andrea; Michel-Schuldt, Michaela; Moyo, Nester T; Bokosi, Martha; Codjia, Laurence; Sharma, Sheetal; Homer, Caroline
Abstract: The 2014 State of the World's Midwifery report included a new framework for the provision of woman-centred sexual, reproductive, maternal, newborn and adolescent health care, known as the Midwifery2030 Pathway. The Pathway was designed to apply in all settings (high-, middle- and low-income countries, and in any type of health system). In this paper, we describe the process of developing the Midwifery2030 Pathway and explain the meaning of its different components, with a view to assisting countries with its implementation. The Pathway was developed by a process of consultation with an international group of midwifery experts. It considers four stages of a woman's reproductive life: (1) pre-pregnancy, (2) pregnancy, (3) labour and birth, and (4) postnatal, and describes the care that women and adolescents need at each stage. Underpinning these four stages are ten foundations, which describe the systems, services, workforce and information that need to be in place in order to turn the Pathway from a vision into a reality. These foundations include: the policy and working environment in which the midwifery workforce operates, the effective coverage of sexual, reproductive, maternal, newborn and adolescent services (i.e. going beyond availability and ensuring accessibility, acceptability and high quality), financing mechanisms, collaboration between different sectors and different levels of the health system, a focus on primary care nested within a functional referral system when needed, pre- and in-service education for the workforce, effective regulation of midwifery and strengthened leadership from professional associations. Strengthening of all of these foundations will enable countries to turn the Pathway from a vision into reality.